SOSIALISASI DAN PENDAMPINGAN PELAYANAN TERTIB ADIMINISTRASI KEPENDUDUKAN DI DESA LEPAK KECAMATAN SAKRA TIMUR - Nur Fitri Eka Asbarini (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2022)
This service is the result of the implementation of a real work course program and collaboration with the Population and Civil Registry Office of East Lombok Regency. The socialization program is a form of population administration service. The document services carried out include Identity Card (KTP), Child Identity Cards (KIA), Death Certificate, Birth Certificate and Family Card (KK). Of course, the implementation of this program is one of the efforts to increase understanding of the public's insight into the importance of having population data. The result of this program is that after participating in the socialization, people who have not completed the previous population administration, then they take care of the population documents assisted by the Population and Civil Registry Office of East Lombok Regency.